Thermal management assembly including intumescent material - Patents.com
The heat management assembly for electric vehicle batteries uses expandable materials with varying expansion temperatures to manage thermal impedance and conductivity, addressing the challenge of thermal runaway propagation and enhancing battery safety and reliability.
Patent Information
- Application Number
- JP2024552673
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-08
- Filing Date
- 2023-03-03
- Publication Date
- 2025-03-21
AI Technical Summary
In electric vehicle batteries, thermal runaway propagation can occur when a single cell's excessive heat causes neighboring cells to fail, leading to catastrophic events. Existing thermal management systems struggle to prevent this cascade effectively.
A heat management assembly is introduced, featuring expandable materials with different expansion temperature ranges disposed between electrochemical cells and heat exchange members. These expandable materials include expandable particles in an organic binder, which expand to increase thermal impedance and then contract to enhance thermal conductivity.
The proposed thermal management assembly effectively delays or prevents thermal runaway propagation by dynamically adjusting thermal impedance and conductivity based on temperature, thereby improving the safety and reliability of electric vehicle batteries.
Smart Images

Figure 2025507987000001_ABST
Abstract
Description
[Background technology]
[0001] Battery life and reliability are key criteria for next generation electric vehicles. These metrics depend on the thermal history that each electrochemical cell in the battery undergoes during operation, because increased temperature can lead to unwanted irreversible electrochemical reactions and reduced capacity. Ideally, therefore, each cell in a battery undergoes the same thermal history and thus ages to the same extent. To achieve this, the battery must be in constant thermal contact during normal operation to increase the effective thermal mass of each cell. This allows any temporary thermal spikes of individual cells to be spread throughout the entire battery module or pack.
[0002] However, in a situation called self-heating, where the heat energy released from the electrochemical reaction exceeds the rate of heat removal, the auto-acceleration of the reaction can result in a catastrophic failure called a runaway event. If this occurs and all cells of the module are in thermal communication, a single cell can initiate runaway of an adjacent cell, accelerating the failure or even burning of the entire pack. The cascade of thermal runaway from one cell to an adjacent cell is called thermal runaway propagation. The industry finds benefit in thermal management assemblies that aim to slow or prevent thermal runaway propagation. Summary of the Invention
[0003] In one embodiment, a thermal management assembly is described that includes a first thermal path including a first expandable material disposed between a first electrochemical cell and a first heat exchange member, and a second thermal path including a second expandable material disposed between a second electrochemical cell and a second heat exchange member, the first and second expandable materials independently including expandable particles dispersed in an organic binder, and the first and second expandable materials expand in a first expansion temperature range and a second expansion temperature range, respectively.
[0004] In some embodiments, the first and / or second expandable material further comprises thermally conductive particles. In some embodiments, one or more (e.g., non-expandable) thermal conductors are in contact with the expandable material.
[0005] In typical embodiments, the first and second heat exchange members are the same heat exchange member and are part of a continuous heat exchange member, hi some embodiments, the first and second intumescent materials are part of a continuous intumescent material.
[0006] When heated to a first temperature in a first expansion temperature range, the first expansible material expands, thereby decreasing the apparent thermal conductivity and increasing the thermal impedance of the first thermal path, in some embodiments, the first expansible material expands and thereby delaminates from the electrochemical cell, the heat exchange member, and / or the thermal conductor.
[0007] When heated to a second, higher temperature, the first expansive material contracts, thereby increasing the apparent thermal conductivity and decreasing the thermal impedance of the first thermal path.
[0008] Methods of using and manufacturing the thermal management assemblies are also described. [Brief description of the drawings]
[0009] Repeat use of reference characters in the specification and drawings is intended to represent the same or similar features or elements of the present disclosure. It is to be understood that those skilled in the art can devise numerous other modifications and embodiments that are within the scope and spirit of the principles of the present disclosure. The figures may not be drawn to scale.
[0010] [Figure 1] 1 is a schematic side view of an exemplary thermal management article including a thermally conductive layer that includes expandable particles. [Diagram 2] 2 is a schematic side view of another thermal management article. [Diagram 3] FIG. 1 is a schematic process flow diagram illustrating thermally induced shear delamination of a thermal management article. [Figure 4] 1 is a graph of thermal impedance as a function of temperature. [Diagram 5] FIG. 5 is a schematic side view showing the thermal paths at different temperatures of an electrochemical cell disposed on a heat exchange member (e.g., a cold plate) having an expandable material with thermal impedance characteristics shown by EX5 in FIG. 4. [Figure 6] 1 is a schematic side view of a thermal management assembly having a thermal path between an electrochemical cell and a heat exchange member. [Figure 7] 1 is a schematic side view of a thermal management assembly having a thermal path between an electrochemical cell and a heat exchange member. [Figure 8] 1 is a schematic side view of a thermal management assembly having a thermal path between an electrochemical cell and a heat exchange member. [Figure 9] 1 is a schematic side view of a thermal management assembly having a thermal path between an electrochemical cell and a heat exchange member. [Figure 10] FIG. 2 is a schematic side view of an exemplary thermal management assembly including additional thermal paths between electrochemical cells. [Figure 11] 11 is a schematic side view of an exemplary composite thermal management article 1100 according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] As used herein, unless otherwise stated, The term "battery module" refers to an assembly of two or more electrically connected electrochemical cells having positive and negative electrodes; The term "thermally conductive" means a thermal conductivity of at least 0.5 watts per meter-Kelvin (i.e., W / mK or equivalently, W m -1 K -1 ) thermal conductivity, The term "thermal impedance" is defined for a thermal path as the sum of the thermal resistance of the material of the path plus any thermal resistance contributions from interfaces made between the material and the heat source and heat sink of the path; The term "apparent thermal conductivity" is defined as the thermal conductivity value calculated from the thermal impedance for the material of the thermal path.
[0012] The features and advantages of the present disclosure will be further understood by consideration of the detailed description and the appended claims.
[0013] Described herein is a thermal management assembly including a first thermal path including a first expandable material disposed between a first electrochemical cell and a first heat exchange member, and a second thermal path including a second expandable material disposed between a second electrochemical cell and a second heat exchange member, wherein the first and second expandable materials independently include expandable particles dispersed in an organic binder, and the first and second expandable materials expand in a first expansion temperature range and a second expansion temperature range, respectively.
[0014] Thus, the thermal management assemblies described herein primarily operate on the principle of expansion.
[0015] The shape of the intumescent material may vary depending on the method of application. For film and sheet materials, including tapes, the intumescent material is typically a thin layer of uniform thickness. The layer may be continuous (in length, width, and thickness) between the electrochemical cell and the heat exchange member. The layer may be continuous or discontinuous with respect to the surface of the heat exchange member. In some embodiments, the electrochemical cell may be contained within the intumescent material, except for the terminals.
[0016] 1, the thermal management article 100 includes an intumescent material 24. The intumescent material 24 includes intumescent particles 45 and thermally conductive particles 46 held in an organic polymer binder 35. Upon heating, the first and second intumescent materials expand in an expansion temperature range due to the expansion of the intumescent particles.
[0017] In some preferred embodiments, shear delamination occurs at the thermally insulating interface due to the expansion of the expansive particles, such that the expanded expansive material delaminates from whatever element it is bonded to and forms the thermally insulating interface. Generally, such shear delamination is readily visually detectable by the unaided human eye having 20 / 20 vision, but can be enhanced by microscopic inspection. Thus, in some embodiments, the thermal management article of FIG. 1 can shear delaminate from the heat exchange member and / or electrochemical cell.
[0018] In other embodiments, the thermal management assembly operates on the principle of shear delamination between two different materials (e.g., intumescent layers) along a thermally insulating interface. Shear delamination occurs when heating to at least the onset temperature range of an expansion temperature range causes the intumescent particles in one of the intumescent materials (e.g., intumescent layers) to expand. This expansion creates a shear strain at the interface, resulting in delamination at the thermally insulating interface and the formation of at least one gap, which increases the thermal resistance across the thermally insulating interface and thus the thermal impedance of the thermal path. Advantageously, shear delamination can occur even when the intumescent material is present as a thin layer, which is suitable for applications where space is limited.
[0019] 2-3, a composite (e.g., multi-layer) thermal management article 200 includes an intumescent material (e.g., layer) 25. The intumescent material 25 includes intumescent particles 45 held in an organic polymer binder 35. A thermally conductive material 15 contacts the intumescent material 25 at a thermally insulating interface 70. Upon heating, the intumescent particles in the intumescent material 25 expand at a temperature in the expansion temperature range. The thermally conductive material (e.g., layer) 15 is typically non-intumescent and does not include intumescent particles. The difference in expansion properties between the intumescent material and the contacting surfaces of the thermal conductor, heat exchange member, and / or electrochemical cell is suitable for the intumescent material to peel off from the contacting surfaces.
[0020] The thickness of the intumescent materials (e.g., intumescent layers) 24 and 25 is typically at least 50, 100, 150, 200, 250, 300, 350, 400, 450, or 500 microns. The thickness of the intumescent materials or layers is typically no greater than 5, 4, 3, 2, or 1 mm.
[0021] 3, in some embodiments, the thermal management article 200 is converted to a thermal management article 200a by heating to at least the minimum onset temperature of the intumescent particles, after which the intumescent particles of the intumescent layer 25 expand to form an intumescent layer 25a that creates shear stress along the thermally insulating interface 70, ultimately causing shear delamination and the formation of gaps 45. This process reduces the heat flow from the intumescent material to the thermally conductive material across the thermally insulating interface (i.e., increases the thermal resistance of the thermally insulating interface). Various embodiments of thermal management assemblies and composite thermal management articles including thermally insulating interfaces are described in PCT / IB2021 / 057275(83207WO003).
[0022] In some embodiments, thermal management articles such as those shown in Figures 1 and 2 may further include an adhesive layer, such as a curable, hot melt, and / or pressure sensitive adhesive. If a pressure sensitive adhesive is present, the article may further include a release liner.
[0023] One embodiment of a composite (e.g., multi-layer) thermal management article further comprising an adhesive is shown in Figure 11. Referring now to Figure 11, a composite thermal management article 1100 includes a layer of intumescent material 25. The intumescent material 25 includes intumescent particles 45 held in an organic polymer binder 35 (see Figure 1). An optional layer of thermally conductive material 15 contacts the layer of intumescent material 25 at a thermally barrier interface 70. A first adhesive layer 1130a, which may be, for example, a hot melt and / or pressure sensitive adhesive layer, is disposed on the layer of thermally conductive material 15 opposite the layer of intumescent material 25. An optional first release liner 1140a is releasably adhered to the adhesive layer 1130a. Optional second adhesive layer 1130b may be, for example, a curable, hot melt and / or pressure sensitive adhesive layer separate from first adhesive layer 1130a and is disposed on the layer of expandable material 25 opposite the layer of thermally conductive material 15. Optional second release liner 1140b is releasably adhered to adhesive layer 1130b. Upon heating, the expandable particles in the layer of expandable material 25 expand. Another embodiment of the thermal management article includes article 100 of FIG. 1 in place of layers 15 and 25 of FIG.
[0024] Pressure sensitive adhesives (e.g., acrylic pressure sensitive adhesives) and hot melt adhesives (e.g., styrene-block-butadiene-block-styrene (SBS) copolymer hot melt adhesives) are widely available from commercial sources, and their selection is within the ability of one of ordinary skill in the art. The composite thermal management article may be provided in any form, for example, a sheet, i.e., a film, a laminate of sheets, or a roll.
[0025] The expandable material may include a composite of an organic polymer and an expandable particle. Exemplary organic polymers include acrylic polymers (e.g., polymethylmethacrylate, polyethylacrylate, polyacrylonitrile), polyolefins (e.g., polyethylene, high molecular weight (HMW) polyethylene, ultra-high molecular weight (UHMW) polyethylene polypropylene, polybutadiene, ethylene-propylene copolymer, and ethylene-propylene diene rubber (EPDM)), styrenic polymers (e.g., polystyrene, acrylonitrile butadiene styrene (ABS), polyvinyl ethers, silicones, polyurethanes, polyethers, polyamines, polyamides, polyesters, polycarbonates, liquid crystal polymers, and combinations thereof. Such materials are widely available from commercial sources. The organic polymers may be linear, chemically crosslinked, or may include a mixture of both types of organic polymers.
[0026] The organic polymer may be a melt-processed (e.g., by extrusion), solvent-based, and / or at least partially cured hardenable resin. If the average number of polymerizable groups per polymerizable compound is greater than one, a chemically crosslinked polymer can be obtained by curing. Suitable hardenable resins include epoxy resins, urethane resins, ring-opening metathesis polymerization (ROMP) cycloolefin resins, isocyanurate resins, free radical polymerizable resins (e.g., mono- and / or multifunctional acrylates, methacrylates, acrylamides, vinyl ethers, and / or maleates), phenolic resins, urea-formaldehyde resins, aminoplast resins, silicone resins, and self-crosslinking polymer latexes. In some cases, curing agents, such as, for example, free radical initiators (thermal initiators or photoinitiators), amine crosslinkers, and / or acid catalysts, are typically used in combination with the hardenable resin. The selection of the hardeners and the relative amounts used, as well as the curing conditions, are within the capabilities of those skilled in the art.
[0027] In some embodiments, the organic binder has a Tg of less than 25° C. or 0° C. In some embodiments, the Tg of the organic binder may be less than −25° C. or −50° C. In this embodiment, the organic polymer may be a free radical curing (e.g., acrylic) polymer. The acrylic polymer may include one or more (meth)acrylate monomers that are cured by exposure to (e.g., ultraviolet) actinic radiation. For example, a homopolymer of ethylhexyl acrylate has a Tg of −50° C. The organic polymer may be characterized as a pressure sensitive adhesive. The acrylic pressure sensitive adhesive may be provided as a film or tape, facilitating the manufacturing process of the thermal management assembly. In this embodiment, the organic polymer is not a moisture curing urethane resin, a (e.g., room temperature) curing epoxy resin, or a cured silicone oil. Thus, in some embodiments, the organic binder does not include a siloxane moiety.
[0028] Expandable particles useful in the practice of the present disclosure are typically particulate materials that expand to many times their original size when heated to a temperature in an expansion temperature range. The expansion temperature range of an expandable particle ranges from a minimum expansion temperature to a maximum expansion temperature. The minimum expansion temperature of the expansion temperature range of an expandable particle typically falls within the onset temperature range T 開始 (or referred to as the expansion onset temperature). The expansion temperature range of the expandable particles also includes a maximum expansion temperature range.
[0029] Examples of expandable particles include thermally expandable polymer microspheres (e.g., available under the trade names EXPANCEL DU from Nouryon (Amsterdam, The Netherlands) and DUALITE U from Chase Corp. (Westwood, Massachusetts), perlite, unexpanded vermiculite, expandable graphite, ammonium polyphosphate, sodium silicate, hydrobiotite, and water-swellable synthetic tetrasilicic fluoride mica as described in US Pat. No. 3,001,571 (Hatch), and combinations thereof. Of these, expandable polymer microspheres are typically preferred when a low onset temperature is desired, or when it is desired that the expansion of the expandable particles occurs at a lower temperature.
[0030] Commercially available grades of DUALITE expandable polymer microspheres include U020-125W(T 開始 =85~90℃);U018-130W(T 開始 = 90 to 95℃, T max =130~140℃);U015-135D(T 開始 = 95 to 100 °C, T max =135~145℃);U024-145W(T 開始 = 115 to 120 °C, T max =145~155℃);U005-190W(T 開始 = 130 to 135 °C, T max =190~200℃);U017-175W(T 開始 = 140 to 145 °C, T max =175~185℃);U010-185W(T 開始 = 145 to 150 °C, T max =185~195℃); and U010-190W(T 開始 = 130 to 135 °C, T max =190-200°C). The same DUALITE expandable polymer microspheres are supplied as wet cake (designation "W") and dry (designation "D"). Commercial grades of EXPANCEL DU expandable polymer microspheres include FG52 DU80 (T 開始=94~105℃), FG92 DU120(T 開始 =122~132℃), 642 WU40(T 開始 =87~93℃), 551 WU40(T 開始 =94~99℃), 461 WU20(T 開始 =100~106℃), and 909 WU80(T 開始 =120 to 130°C).
[0031] Commercial grades of expandable polymer microspheres typically have an onset temperature of at least 80 or 85° C. The maximum temperature of the expansion temperature range is typically no greater than 285, 275, or 250° C. In some embodiments, the expansion temperature range has a maximum value less than 250, 225, 200, or 175° C. In some embodiments, the expansion temperature range has a maximum value less than 155, 150, 145, or 140° C. In some embodiments, the expansion temperature range of the expandable particles has an onset temperature range with a minimum value less than 110, 105, 100, 95, 90, 85, or 80° C.
[0032] The expansion temperature range of the expandable microspheres is related to the size of the expandable microsphere, the blowing agent inside the microsphere, the shell thickness, and the shell material. For example, an acrylonitrile copolymer shell typically has a higher onset temperature range than a polyvinylidene dichloride shell. Thus, in some preferred embodiments, the expandable material comprises an expandable polymer microsphere that includes a polyvinylidene dichloride shell.
[0033] An intumescent material can also be described by its expansion temperature range (the expansion temperature range of the intumescent material). The expansion temperature range of an intumescent material ranges from a minimum expansion temperature to a maximum expansion temperature. The minimum expansion temperature of the expansion temperature range of an intumescent material is typically the starting temperature range T 開始 (or expansion onset temperature). The expansion temperature range of the expandable material also includes a maximum expansion temperature range. In some embodiments, the expansion temperature range of the expandable material is the same as the onset temperature range of the expandable particles (e.g., expandable polymer microspheres).
[0034] In other embodiments, the expansion temperature range of the expandable material is a range that includes the onset temperature range and maximum temperature range of the expandable particles (eg, expandable polymer microspheres).
[0035] A lower onset temperature range is suitable for delaying or preventing thermal runaway at lower temperatures. Thus, the expansion of the expandable particles occurs faster as a function of time. The expandable polymer microspheres can be characterized as irreversibly expandable above their onset temperature. After expansion, simply lowering the temperature typically does not cause the polymer microspheres to significantly shrink to their unexpanded size. However, as evidenced by FIG. 4, increasing the temperature of the expanded material to a second, higher temperature (e.g., above the onset temperature range) can cause a decrease in thermal impedance. Thus, at such a second, higher temperature, the expandable microspheres collapse and / or shrink in size. In some embodiments, the expandable polymer microspheres may be at least partially melted. The expandable material including the collapsed and / or shrunk polymer microspheres also has a higher density compared to the expandable material at the onset temperature range.
[0036] When the electrochemical cell is heated to a second, higher temperature, the expandable material contracts, thereby increasing the apparent thermal conductivity. The (e.g., first) thermal path has a reduced thermal impedance. The second temperature is typically higher than the initiation temperature range of the expandable polymer microspheres. In some embodiments, the second temperature is higher than the maximum temperature of the expansion temperature range. In some embodiments, the second (e.g., contraction) temperature is less than 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, or 110° C. Preferably, the binder material is capable of deforming when the expandable microspheres collapse at the second temperature. Furthermore, if the expandable material shears away (e.g., at a thermally insulable interface), thermal contact is preferably re-established at the second temperature.
[0037] Pressure may be applied (e.g., uniaxially) to the expansive material to enhance the contraction of the expansive particles and / or re-establish thermal contact of the thermally blocked interface at the second temperature. The applied pressure may be at least 1, 2, 3, 4, or 5 kPa, and is typically no greater than 1 MPa, 500 kPa, 100 kPa, 50 kPa, 25 kPa, or 15 kPa. In some embodiments, the pressure is applied by the weight (mass and gravity) of the electrochemical cells on the expansive material. In a typical embodiment, the thermal management assembly is within the housing of the battery module. In this embodiment, the pressure may be applied by the overall thermal expansion of the thermal management assembly constrained by the housing.
[0038] Thus, while the thermal management assembly initially operates on the principle of expansion, the thermal management assembly also operates on the principle of contraction, which is suitable for increasing the apparent thermal conductivity of the expansive material and reducing the thermal impedance of the thermal path at temperatures higher than the expansion temperature range of the expansive material.
[0039] Referring to FIG. 4 and Table 3, the intumescent material first reduces the apparent thermal conductivity, thus reducing the thermal impedance of the thermal path to at least 1E-03 (i.e., 1×10 -3 )m 2 In some embodiments, the increase in thermal impedance can be at least 2E-03 m 2 K / W, 3E-03m 2 K / W or 4E-03m 2 The intumescent material can also reduce the apparent thermal conductivity and thus the thermal impedance of the thermal path at the second, higher temperature. At such second, higher temperature, the intumescent material can reduce the thermal impedance by at least 1E-03 (i.e., 1×10 -3 )m 2 In some embodiments, the reduction can be at least 2E-03 m 2 K / W, 3E-03m 2 K / W or 4E-03m 2 It is K / W.
[0040] With reference to Table 4, the thermal pathway increases the thermal impedance by at least 50, 100, 200, 300, or 400% when the expandable particles and expandable material are expanding at a temperature in the expansion (e.g., onset) temperature range of the expandable material. The thermal pathway decreases the thermal impedance by at least 25, 50, or 75% when the expandable particles and expandable material are contracting at a temperature above the expansion temperature range of the expandable material.
[0041] The expandable material of EX-5 in FIG. 4 includes expandable polymer microspheres that are reported to have an expansion onset temperature of 90-95°C and a maximum expansion temperature of 130-140°C. Notably, the thermal impedance increases sharply at 80°C. The thermal impedance peaks at the highest value of the onset temperature range for the expandable microspheres. In this particular embodiment, the thermal impedance does not increase at temperatures above 95°C in the 130-140°C range. Notably, a decrease in thermal impedance occurs when the temperature is higher than the highest temperature of the onset temperature range (95°C in this example). Thus, in this embodiment, the expandable polymer microspheres have not expanded over the entire expansion temperature range reported for expandable polymer microspheres. Furthermore, the expansion temperature range of the expandable material is not the same as the expansion temperature range of the expandable polymer microspheres. Without wishing to be bound by theory, it is speculated that the expansion properties of the expandable polymer microspheres are influenced by i) the shell material and blowing agent of the expandable polymer microspheres, ii) the organic resin of the expandable material surrounding the expandable polymer microspheres, and iii) any pressure applied to the expandable material containing the expandable polymer microspheres. Thus, depending on these factors, it is speculated that other expandable polymer microspheres incorporated into the expandable material and possibly subjected to the application of pressure may expand at a temperature higher than the onset temperature but lower than the maximum expansion temperature.
[0042] Referring to FIG. 5(a), when the temperature of the thermal management assembly is less than the expansion temperature (<T1) of the expandable material 625 disposed between the electrochemical cells 610, 611, 612, and 613 and the heat exchange member 650, each of the heat paths indicated by the arrows extends from the electrochemical cell through the expandable material 625 to the heat exchange member and is characterized as “on”. The expandable material 625 can be the expandable material 24 or the expandable material 25. In some embodiments, the first and second expandable materials are part of a continuous expandable material, such as a continuous layer, as shown in FIG. 5. Alternatively, the first and second expandable materials may be discontinuous, as shown in FIGS. 6-10. As shown in FIGS. 6-10 below, there may be one or more heat conductors and two or more expandable materials. Referring to FIG. 5(b), when the temperature of the electrochemical cell 611 begins to overheat and reaches the expansion temperature range (T1) of the expandable particles and the expandable material 625 expands, thereby reducing the apparent thermal conductivity and increasing the thermal impedance of the heat path between such an electrochemical cell 611 and the heat exchange member 650. The decrease in apparent thermal conductivity and the increase in thermal impedance are indicated by “X” in FIG. 5(b) and can also be characterized as switching the heat path “off”. Referring to FIG. 5(c), when the temperature of the electrochemical cell 611 continues to overheat and reaches a temperature (referred to herein as the second temperature) higher than the maximum expansion temperature (T2) of the expansion material 625, the expandable material contracts, thereby increasing the apparent thermal conductivity and decreasing the thermal impedance of the heat path between such an electrochemical cell 611 and the heat exchange member 650. Accordingly, this heat path is switched “on” again and is indicated by the arrow extending from the electrochemical cell 611 through the expandable material to the heat exchange member in FIG. 5(c). Accordingly, excess heat can again be transferred to the heat exchange member and its optional coolant. Referring further to FIG. 5(c), the expandable material 625 disposed within the heat path between the heat exchange member and the adjacent cells 610 and 612 reaches the expansion temperature range (T1) of the expandable material. Thereby, the expandable material 625 expands, thereby reducing the apparent thermal conductivity and / or increasing the thermal impedance of the heat path between such electrochemical cells 610 and 612 and the heat exchange member 650.That is, the thermal path of one or more electrochemical cells (eg, 610, 612) is switched off at the same time that the thermal path of one or more other electrochemical cells (eg, 611) is switched on.
[0043] Inorganic expandable particles, such as perlite, unexpanded vermiculite, expandable graphite, ammonium polyphosphate, sodium silicate, hydrobiotite, and water-swellable synthetic fluorotetrasilicic mica, typically have a much higher expansion temperature range than expandable polymer microspheres. Inorganic expandable particles also typically have a higher decomposition temperature. For example, graphite decomposes at 700-900°C. Furthermore, inorganic expandable particles may not shrink at temperatures suitable to allow reconnection of the thermal pathway between the electrochemical cell and the heat exchange member. Thus, the presence of inorganic expandable particles may impair physical properties that reduce thermal impedance and increase apparent thermal conductivity at lower temperatures. Thus, in a preferred embodiment, the expandable material comprises expandable polymer microsphere particles dispersed in an organic binder, and little or no non-conductive inorganic expandable particles, such as expandable graphite. Thus, in some embodiments, the concentration of such inorganic expandable particles (e.g., expandable graphite) is typically less than 30, 25, 20, 15, 10, 5, or 1 weight percent of expandable graphite, based on the total amount of expandable particles. In these embodiments, the expandable material typically comprises more than 70, 75, 80, 85, 90, 95, or 99 weight percent of polymer microspheres, based on the total amount of expandable particles.
[0044] The expandable particles may have any desired particle size. In some embodiments, the expandable particles have a volume average particle size ranging from 0.01 to 500 microns, preferably 0.1 to 150 microns. The amount of expandable particles is typically at least 10 volume percent, at least 20 volume percent, at least 30 volume percent, at least 40 volume percent, or even more preferably greater than 50 volume percent, based on the total volume of the expandable material.
[0045] The weight percentage of the expandable particles may vary depending on the density. In the case of expandable polymer microspheres, the amount of expandable polymer microspheres is typically at least 0.1, 0.2, 0.3, 0.5, 0.5, 0.6, 0.7, 0.8, 0.9, or 1% by weight of the expandable material. In some embodiments, the expandable polymer microspheres are at least 2, 3, 4, or 5% by weight of the expandable material. In some embodiments, the expandable polymer microspheres are at least 10, 15, or 20% by weight of the expandable material. Expandable polymer microspheres typically have a density of about 1 g / cc before expansion. Thus, 50 volume percent of expandable polymer microspheres is equivalent to about 50 weight percent of expandable polymer microspheres when dispersed in a polymer binder with the same density. In some embodiments, the amount of expandable polymer microspheres is no more than 45, 40, 35, 30, 25, or 20% by weight of the expandable material. The amount of expandable polymer microspheres can depend on whether the expandable material is single layer, as shown in Figure 1, or multi-layer, as shown in Figure 2. If single layer, the volume percent of expandable microspheres is typically lower than the thermal filler, so that the expandable material is also sufficiently thermally conductive. In this embodiment, the amount of expandable polymer microspheres is typically less than 25 volume percent.
[0046] The intumescent material, when present in the thermal pathway, may have a lower apparent thermal conductivity than the thermally conductive material (e.g., layer), but this is not a requirement. In such embodiments, the intumescent material may have an apparent thermal conductivity that is 0.9, 0.75, 0.5, or even 0.05 times the apparent thermal conductivity of the thermally conductive material (e.g., layer).
[0047] In some embodiments, a thermally conductive material is present. For example, the expandable material of FIG. 1 may include thermally conductive fillers in combination with expandable particles and may therefore be characterized as a thermally conductive material. As yet another example, a (non-conductive) expandable material (e.g., layer) 25 may be provided in a separate layer disposed above a thermally conductive material (e.g., layer) 15, as shown in FIG. 2. The thermally conductive material (e.g., layer) and / or the thermally conductive expandable material, or a composite of a thermally conductive material and a (e.g., non-conductive) expandable material, may have a thermal conductivity of at least 0.5 watts per meter Kelvin (i.e., W / mK or equivalently, Wm -1 K -1 ), more preferably at least 1 Wm -1 K -1 , at least 2.5Wm -1 K -1 , at least 5Wm -1 K -1 , at least 10Wm -1 K -1 , at least 15Wm -1 K -1 , at least 20Wm -1 K -1 , or at least 30Wm -1 K -1 However, this is not a requirement, especially when present as a thin layer.
[0048] The thermally conductive material may include, for example, an organic polymer binder, as described with respect to the intumescent material.
[0049] In some embodiments, the expandable material and / or the thermally conductive material further comprises thermally conductive filler particles (i.e., thermal fillers). Any thermally conductive filler can be used, including, for example, particles comprising at least one of aluminum oxide (alumina), magnesium oxide, aluminum hydroxide, silicon nitride, zinc oxide, silicon oxide, beryllium oxide, titanium oxide, copper oxide, cuprous oxide, boron nitride, aluminum nitride, silicon carbide, diamond, talc, mica, kaolin, bentonite, magnesite, pyrophyllite, titanium boride, calcium titanate, metals (e.g., copper, aluminum, brass, steel, bronze), graphite, carbon black, graphene, and combinations thereof.
[0050] The thermally conductive filler can have any desired particle size. In some embodiments, the thermal filler has a volume average particle size ranging from 0.01 to 500 microns, preferably 0.1 to 150 microns. When present, the amount of thermal filler is typically greater than 30 volume percent, preferably greater than 40 volume percent, more preferably greater than 50 volume percent, based on the total volume of the thermally conductive material.
[0051] Suitable thermal fillers are readily available from commercial suppliers and can optionally be processed (eg, milled and / or classified) to provide the desired average particle size.
[0052] The intumescent material and / or the thermally conductive material may further include additives, if desired, such as, for example, antioxidants, UV stabilizers, fillers, plasticizers, colorants, flame retardants, and fragrances.
[0053] In some preferred embodiments, the expansive material and / or the thermally conductive material comprises a thin layer (e.g., has the form of a thin layer). These embodiments are advantageous because the in-plane expansion (i.e., causing shear forces) remains constant, but the thickness expansion is minimized, allowing for use in constrained spaces.
[0054] Preferably, the apparent thermal conductivity between the first electrochemical cell and the heat exchange member (e.g., a heat sink) decreases by at least 50 percent, at least 75 percent, or even at least 90 percent at or above the expansion temperature range of the expansive material.
[0055] Preferably, the thermal impedance between the first electrochemical cell and the heat exchange member (eg, a heat sink) decreases by at least 50 percent, at least 75 percent, or even at least 90 percent above the expansion temperature of the expansible material.
[0056] In some embodiments, the thermal management assembly includes a thermal path having a thermal impedance in the temperature range of 50-90° C. that is at least 25% less than the thermal impedance in the temperature range of 90-110° C. In some embodiments, the thermal impedance in the temperature range of 50-90° C. may be at least 30, 40, 50, 60, or 70% less than the thermal impedance in the temperature range of 90-110° C. This same reduction in thermal impedance can be obtained at other temperatures depending on the selection of the expansive material.
[0057] In some embodiments, the thermal management assembly includes a thermal path having a thermal impedance in the temperature range of 120-170° C. that is at least 25% less than the thermal impedance in the temperature range of 80-90° C. In some embodiments, the thermal impedance in the temperature range of 120-170° C. may be at least 30, 40, 50, or 60% less than the thermal impedance in the temperature range of 80-90° C. This same reduction in thermal impedance can be obtained at other temperatures depending on the selection of the expansive material.
[0058] In embodiments having an intumescent material and a thermally conductive material (e.g., a layer), the combined volume of the layers preferably increases by less than 50 percent, less than 25 percent, or even less than 10 percent over the expansion temperature range of the intumescent material.
[0059] In embodiments having multiple expandable material layers, each containing respective expandable particles, it is contemplated that the respective expandable particles in each expandable material layer may have the same or different onset temperatures.
[0060] The thermal management assemblies described herein include at least two electrochemical cells.
[0061] In some embodiments, the thermal management assemblies described herein include a plurality of electrochemical cells. For example, a battery module for an electric vehicle often has tens to hundreds of electrochemical cells. In some embodiments, two or more electrochemical cells each have a thermal path to the same heat exchange member, such as those shown in Figures 6-10. In other less typical embodiments, two or more electrochemical cells have a thermal path to separate heat exchange members.
[0062] While any type of electrochemical cell (e.g., galvanic, voltaic, electrolytic, and fuel cells) may be used, the present disclosure may have particular applicability to rechargeable electrochemical cells. Exemplary rechargeable electrochemical cells include nickel cadmium (NiCd) cells, nickel metal hydride (NiMH) cells, lithium ion (Li-ion) cells, lithium iron phosphate (LiFePO4) cells, and lithium ion polymer (Li-ion polymer) cells. Of these, lithium-containing rechargeable electrochemical cells and batteries containing them are known to undergo accidental thermal runaway events due to, for example, internal short circuits, overcharging, and / or physical damage. To reduce these events, and for convenience, electrochemical cells (except for the terminal electrodes) are often enclosed and sealed within a casing (battery). Any type of electrochemical cell may be used, including, but not limited to, cylindrical cells, prismatic cells, and pouch cells.
[0063] The heat exchange member may be a heat sink, i.e., a device or substance for absorbing excess or unwanted heat from a heat source. Typically, a heat sink is a passive heat exchanger that transfers heat generated by an electronic or mechanical device to a fluid medium, often air or a liquid coolant, so that the heat can be dissipated from the device, thereby allowing regulation of the temperature of the device, although this is not a requirement. In electronic devices, heat sinks are usually designed to maximize the surface area in contact with the cooling medium that surrounds the heat sink, such as air.
[0064] Air velocity, material selection, protrusion design and surface treatment are factors that affect the performance of the heat sink. Thermal adhesives or thermal greases improve the performance of the heat sink by filling the gap between the heat sink and the heat spreader (e.g., fins) on the device. Heat sinks are often made from aluminum or copper, although other materials may be used.
[0065] The heat exchanger may be an active heat exchanger with a circulating coolant. In the present invention, the heat exchanger is not another electrochemical cell. However, the thermal management assembly described herein may also have a third thermal path between the electrochemical cells, as shown in FIG. 10. The third thermal path 663 may include an intumescent material 625 described herein between the electrochemical cells in addition to having an intumescent material between the electrochemical cells and the heat exchange member.
[0066] 6, a thermal management assembly 600 includes a first electrochemical cell 610 and a second electrochemical cell 611. An intumescent material 625 is disposed between each electrochemical cell and a heat exchange member 650. The intumescent material 625 (as shown by the thermal management article 100 of FIG. 1) includes thermally conductive particles and intumescent particles (both not shown) held in an organic polymer binder. The intumescent material 625 typically contacts and conforms to surfaces of both the electrochemical cells and the heat exchange member. Thermal pathways 661 and 662 extend from the electrochemical cells through the intumescent material 625 to the heat exchange member 650.
[0067] 7, the thermal management assembly 700 includes a first electrochemical cell 610 and a second electrochemical cell 611. A thermal conductor (e.g., layer) 715 and an intumescent material (e.g., layer) 725 are disposed between each electrochemical cell and a heat exchange member 650. Thermal paths 661 and 662 extend from the electrochemical cells through the thermal conductor (e.g., layer) 715 and the intumescent material (e.g., layer) 725 to the heat exchange member 650.
[0068] 8 illustrates another thermal management assembly 800. The thermal management assembly 800 is similar to that of FIG 7 and includes a thermal conductor (e.g., layer) 715a between the electrochemical cells 610 and 611 and an intumescent material (e.g., layer) 725, and a second thermal conductor layer 715b between the intumescent material (e.g., layer) 725 and the heat exchange member 650.
[0069] 9 illustrates another thermal management assembly 900. The thermal management assembly 900 is similar to that of FIG. 8 and includes an intumescent material (e.g., layer) 725a between the electrochemical cells 610 and 611 and the thermal conductor layer 715, and an intumescent material (e.g., layer) 725b between the thermal conductor layer 715 and the heat exchange member 650.
[0070] FIG. 10 shows another thermal management assembly 1000. The thermal management assembly 1000 is similar to FIG. 6 and further includes an intumescent material 625 between the electrochemical cells. The intumescent material 625 between the electrochemical cells 610, 611 and the heat exchange member 650 is interspersed (not shown) in the heat exchange member 650. The intumescent material between the electrochemical cells can be the thermal management article of FIG. 1 or FIG. 2. The intumescent material between the electrochemical cells can further include an additional thermal conductor or intumescent layer such as those shown in FIG. 7, FIG. 8 and FIG. 9. An additional (e.g., third) thermal path 663 extends from the electrochemical cell 610 to the electrochemical cell 611.
[0071] In some embodiments, the first and second intumescent materials are portions of a discontinuous intumescent material, such as continuous layers, as shown in Figures 6-10. Alternatively, the first and second intumescent materials may be continuous, as shown in Figure 5.
[0072] In the exemplary embodiment shown in Figures 6-10, the intumescent materials between the first and second electrochemical cells and the heat exchange member are shown as being the same, it is understood that the intumescent materials may be different.
[0073] The present invention also relates to a method of manufacturing a thermal management assembly, comprising providing an expandable material (e.g., a first) between a first electrochemical cell and a heat exchange member, and providing an expandable material (e.g., a second) between a second electrochemical cell and a heat exchange member, the expandable material comprising expandable particles that expand in an expansion temperature range described herein, hi some embodiments, the expandable material is provided as a sheet, film, or tape.
[0074] The present invention also relates to a method of using a thermal management assembly, the method comprising: i) providing a thermal management assembly as described herein and illustrated in Figures 5-11; ii) exposing a first and a second thermal path to a temperature within an initiation temperature range; and iii) exposing the first thermal path to a second temperature above the expansion temperature range while the second thermal path of a second electrochemical cell is within an expansion temperature range, thereby decreasing the thermal impedance of the first thermal path and increasing the thermal impedance of the second thermal path.
[0075] Objects and advantages of the present disclosure are further illustrated by the following non-limiting examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit the disclosure. EXAMPLES
[0076] Unless otherwise stated, all parts, percentages, ratios, etc. in the examples and elsewhere in this specification are by weight. [Table 1]
[0077] Base syrup The base syrup was prepared by combining 350 g of EHA and 0.14 g of IRG651 in a 1-quart glass jar and mixing with a high shear electric motor until a homogenous mixture was obtained. The resulting mixture was degassed for 5 minutes by bubbling nitrogen gas through a tube inserted in the opening of the lid. With stirring, the mixture was exposed to UVA light until a pre-adhesive syrup was formed with a viscosity deemed suitable for coating. After UV exposure, air was introduced into the jar. This prepolymer was then mixed with 0.22 parts per hundred (phr) of HDDA and 0.43 phr of IRG819 to form the final base syrup formulation.
[0078] Comparative Example (Non-Expanding) Non-Conductive Layer The base syrup was coated between two RF32N liners using a notched bar coater with a nominal gap of 100 microns. The coating was cured by exposing the PET surface to UVA energy.
[0079] (Non-expandable) thermally conductive layer The coating solution was prepared by mixing 12.6 parts by weight of base syrup, 52.4 parts by weight of BAK70, 17.5 parts by weight of BAK10, and 17.5 parts by weight of TM1250 under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 500 microns. The coating was cured by exposing the PET surface to UVA energy.
[0080] Expandable layer A The coating solution was prepared by mixing 95.2 parts by weight of base syrup and 4.8 parts by weight of U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 100 microns. The coating was cured by exposing the PET surface to UVA energy.
[0081] Expandable layer B The coating solution was prepared by mixing 90.9 parts by weight of base syrup and 9.1 parts by weight of U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 100 microns. The coating was cured for 15 minutes by exposing the PET surface to UVA energy.
[0082] Expandable layer C The coating solution was prepared by mixing 87.0 parts by weight of base syrup and 13.0 parts by weight of U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 100 microns. The coating was cured by exposing the PET surface to UVA energy.
[0083] Expandable layer D The coating solution was prepared by mixing 83.3 parts by weight of base syrup and 16.7 parts by weight of U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 100 microns. The coating was cured by exposing the PET surface to UVA energy.
[0084] Expandable layer E The coating solution was prepared by mixing 80.0 parts by weight of base syrup and 20.0 parts by weight of U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 100 microns. The coating was cured by exposing the PET surface to UVA energy.
[0085] Example 1 (EX-1) An approximately 2 inch by 2 inch (5.1 cm by 5.1 cm) square was cut from the cured intumescent layer A and two 2 inch by 2 inch (5.1 cm by 5.1 cm) squares were cut from the cured thermally conductive layer.
[0086] After removing the PET liner from one side of the intumescent layer A and one of the squares of the thermally conductive layer, the squares were laminated together using a hand-held roller to remove the air. The PET liner was then removed from the exposed side of the intumescent layer and from one side of the remaining thermally conductive layer square. The thermally conductive layer was then laminated to the exposed side of the intumescent layer using a hand-held roller to obtain the final multi-layer structure.
[0087] Example 2 (EX-2) EX-2 was constructed following the same procedure as EX-1, except intumescent layer B was used instead of intumescent layer A.
[0088] Example 3 (EX-3) EX-3 was constructed following the same procedure as EX-1, except intumescent layer C was used instead of intumescent layer A.
[0089] Example 4 (EX-4) EX-4 was constructed following the same procedure as EX-1, except intumescent layer D was used instead of intumescent layer A.
[0090] Example 5 (EX-5) EX-5 was constructed following the same procedure as EX-1, except intumescent layer E was used instead of intumescent layer A.
[0091] Example 6 (EX-6) EX-6 was EX-1 constructed as a single expandable layer. The coating solution consisted of 6.25 g base syrup, 20.25 g BAK70, 6.75 g BAK10, 6.75 g TM1250, and 0.064 g U018-130D. It was prepared by mixing under high shear and partial vacuum (10 mbar). The solution was coated between two RF32N liners using a notched bar coater with a nominal gap of 500 microns.
[0092] The coating was cured by exposing the PET surface to UVA.
[0093] Example 7 (EX-7) EX-7 was EX-2 constructed as a single expandable layer. The coating solution was prepared by mixing 6.25g base syrup, 20.25g BAK70, 6.75g BAK10, 6.75g TM1250, 0.122g U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 500 microns. The coating was cured by exposing the PET surface to UVA.
[0094] Example 8 (EX-8) EX-8 was EX-3 constructed as a single expandable layer. The coating solution was prepared by mixing 6.25g base syrup, 20.25g BAK70, 6.75g BAK10, 6.75g TM1250, and 0.176g U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 500 microns. The coating was cured by exposing the PET surface to UVA.
[0095] Example 9 (EX-9) EX-9 was EX-4 constructed as a single expandable layer. The coating solution was prepared by mixing 6.25g of base syrup, 20.25g of BAK70, 6.75g of BAK10, 6.75g of TM1250, and 0.224g of U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 500 microns. The coating was cured by exposing the PET surface to UVA energy.
[0096] Example 10 (EX-10) EX-10 was EX-5 constructed as a single expandable layer. The coating solution was prepared by mixing 6.25g of base syrup, 20.25g of BAK70, 6.75g of BAK10, 6.75g of TM1250, and 0.269g of U018-130D under high shear and partial vacuum (10 mbar). The solution was then coated between two RF32N liners using a notched bar coater with a nominal gap of 500 microns. The coating was cured by exposing the PET surface to UVA energy.
[0097] Comparative example 1 (CE-1) CE-1 was a multi-layer structure that did not contain an intumescent material. CE-1 was constructed by cutting an approximately 2.5" x 2.5" (6.4cm x 6.4cm) square from the cured comparative non-conductive layer, and two 2.5" x 2.5" (6.4cm x 6.4cm) squares were cut from the cured thermally conductive layer. The PET liner was removed from one side of the comparative non-conductive layer and one of the thermally conductive layer squares, and then the squares were laminated together using a hand-held roller to remove air. The PET liner was then removed from the exposed side of the comparative non-conductive layer and from one side of the remaining thermally conductive layer square. The thermally conductive layer was then laminated to the exposed side of the comparative non-conductive layer using a hand-held roller to obtain the final multi-layer structure.
[0098] Comparative example 2 (CE-2) CE-1 was a thermally conductive layer that did not contain any intumescent material. CE-2 was constructed by laminating four layers of the thermally conductive layer together.
[0099] Test Method Measurement of apparent thermal conductivity Apparent thermal conductivity was determined according to the following procedure. Circular disks with a diameter of 33 mm were punched out of the layers or multi-layer structures either before or after thermal expansion. After the release liners were removed from both sides of the punched samples, the disks were placed on the bottom plate of a TIM tester (Analysis Tech, Wakefield, Massachusetts) and the top plate was slowly lowered to contact the top surface of the sample, applying minimal allowable pressure (less than 10 psi). The top plate was heated and the bottom plate was cooled until a temperature gradient was established with an average sample temperature of 50°C. Apparent thermal conductivity was calculated by dividing the sample thickness by the thermal impedance. The reported values include the contact resistance from the interface between each plate and the sample surface.
[0100] Expansion rate Circular disks with a diameter of 33 mm were punched out of the multi-layered structure. The disks were placed in an aluminum pan and placed in a batch oven set at 130° C. After 5 minutes, the samples were removed and the apparent thermal conductivity was measured according to the method described above. The results are reported in Table 2.
[0101] In Table 2, all examples show a decrease in thermal conductivity after expansion and an apparent thermal conductivity ratio of less than 1. In particular, the multilayer samples that show significant delamination after expansion (i.e., EX-4 and EX-5) show a larger decrease in thermal conductivity and a lower thermal conductivity ratio compared to the same compositions prepared as single layers (i.e., EX-9 and EX-10). [Table 2]
[0102] Thermal impedance measurement The face thickness thermal impedance of the samples was determined according to the following procedure in accordance with ASTM E1530. A circular disk with a diameter of 50 mm was punched out of the multi-layer structure. The release liners were removed from both sides and replaced with a thin film of copper foil (0.025 mm). The sample was then placed on the bottom plate of a DTC-300 (TA Instruments, New Castle, Delaware) and the top plate was lowered with an applied pressure of 100 kPa or with the top plate air pressure removed, as described in each example or comparative example, to contact the top surface of the sample (for any test without applied pressure, the pressure was relaxed to about 11 kPa (determined by estimating the weight of the test head)). The top and bottom plates were then temperature controlled. For each thermal impedance measurement, a temperature gradient was established to achieve a 30°C difference across the sample with the top plate being the hotter side relative to the bottom plate. Measurements of heat flow across the sample were performed successively at the following average sample temperatures: 50, 70, 80, 90, 100, 110, 120, 140 and 160 °C. A guard heater around the sample was also heated to the average sample temperature for each measurement. Heat flow measurements were performed after thermal equilibrium was established (approximately 1 h later). Thermal impedance (I) was calculated based on the area of the heating plate (A), the measured temperature difference (ΔT) and the measured heat flow (Q): I = A · ΔT · Q -1 The thermal impedance is defined as the sum of the thermal resistance of the sample plus any contact resistance contribution from the interfaces (e.g., plate / copper foil, copper foil / sample). The thermal impedance at various temperatures is reported in Table 3. The percentage change is (I 最終 -I 初期 ) / I 初期 * is defined as 100. The percent changes in the temperature ranges of 50-90°C and 90-110°C for the examples and comparative examples are shown in Table 4. [Table 3] [Table 4]
Claims
1. 1. A thermal management assembly comprising: a first thermal path including a first expansible material disposed between the first electrochemical cell and the first heat exchange member; a second thermal path including a second expansible material disposed between the second electrochemical cell and the second heat exchange member; a thermal management assembly, the first and second expandable materials independently comprising expandable particles dispersed in an organic binder, the first and second expandable materials expanding in a first expansion temperature range and a second expansion temperature range, respectively.
2. The thermal management assembly of claim 1 , wherein the first and / or second expansive materials further comprise thermally conductive particles.
3. The thermal management assembly of claim 1 or 2, further comprising one or more thermal conductors in contact with the expansive material.
4. The thermal management assembly of any one of claims 1 to 3, wherein the first and second intumescent materials are part of a continuous intumescent material.
5. The thermal management assembly of any one of claims 1 to 4, wherein the first and second heat exchange members are part of a continuous heat exchange member.
6. 6. The thermal management assembly of claim 1, wherein when heated to a first temperature in the first expansion temperature range, the first expansive material expands, thereby decreasing an apparent thermal conductivity and increasing a thermal impedance of the first thermal path.
7. 7. The thermal management assembly of claim 1, wherein when heated to a first temperature in the first expansion temperature range, the first expandable material expands, such that the first expandable material peels off from the first electrochemical cell, the first heat exchange member, and / or the thermal conductor.
8. The thermal management assembly of any one of claims 1 to 7, wherein the first and second expansion temperature ranges of the first and second expansive materials are in the range of 80°C to 285°C.
9. The thermal management assembly of any one of claims 1 to 8, wherein the expandable particles have an expansion temperature range having a maximum temperature less than 155, 150, 145, or 140°C.
10. The thermal management assembly of any one of claims 1 to 9, wherein the expandable particles have an expansion temperature range with an onset temperature range having a minimum temperature less than 110, 105, 100, 95, 90, 85, or 80°C.
11. 11. The thermal management assembly of claim 1, wherein when heated to a second temperature higher than the first expansion temperature range, the first expansive material contracts, thereby increasing an apparent thermal conductivity and decreasing a thermal impedance of the first thermal path.
12. The thermal management assembly of claim 11 , wherein the second temperature is less than 180, 170, 160, 150, 140, 130, 120, 110, or 100 degrees Celsius.
13. 13. The thermal management assembly of claim 11 or 12, wherein during a thermal runaway, the first expansive material reaches the second temperature while the second expansive material is within the second expansion temperature range, thereby decreasing the thermal impedance of the first thermal path and increasing the thermal impedance of the second thermal path.
14. The thermal management assembly of any one of claims 1 to 13, wherein the first and / or second expandable materials comprise expandable polymer microspheres.
15. 15. The thermal management assembly of claim 1, wherein the first and / or second expandable material comprises greater than 70, 75, 80, 85, 90, 95, or 99 weight percent expandable polymer microspheres based on the total amount of expandable particles.
16. 16. The thermal management assembly of claim 1, wherein the first and / or second expandable material comprises less than 30, 25, 20, 15, 10, 5, or 1 weight percent expandable graphite, based on the total amount of expandable particles.
17. The thermal management assembly of any one of claims 2 to 16, wherein the organic binder comprises an acrylic polymer.
18. The thermal management assembly of any one of claims 2 to 17, wherein the organic binder is free of siloxane moieties and has a Tg less than 0°C.
19. The thermal management assembly of any one of claims 2 to 18, wherein the organic binder is a pressure sensitive adhesive.
20. 20. The thermal management assembly of any one of claims 1 to 19, wherein the first and / or second expandable materials are in the form of one or more layers of films or sheets, said forms including multi-layer films and multi-layer sheets.
21. The thermal management assembly of claim 20 , wherein the multilayer film comprises a layer of the first and / or second expandable material disposed adjacent to one or more thermal conductor layers.
22. 22. The thermal management assembly of claim 1, wherein the first and / or second expandable materials have an apparent thermal conductivity that decreases by at least 50, 75, or 90 percent with temperatures in the first and / or second expansion temperature ranges.
23. 22. The thermal management assembly of claim 1, wherein when the expansive particles are expanding, a thermal impedance of the first and / or second thermal pathways increases by at least 50, 100, 200, 300, or 400%, and when the expansive particles are contracting, a thermal impedance of the thermal pathways decreases by at least 25, 50, or 75%.
24. The thermal management assembly of any one of claims 1 to 23, wherein the thermal management assembly further comprises an expandable material comprising expandable particles between the first and second electrochemical cells.
25. 1. A method of using a thermal management assembly, comprising: i) providing a thermal management assembly according to any one of claims 1 to 24; ii) exposing the first thermal path to a first temperature in the first expansion temperature range such that a thermal impedance of the first thermal path increases; iii) exposing the first thermal path to a second temperature higher than the first expansion temperature range while the second thermal path is within the second expansion temperature range, thereby decreasing the thermal impedance of the first thermal path and increasing the thermal impedance of the second thermal path.
26. 26. The method of claim 25, further comprising applying a pressure to the first expansive material in the range of 1 kPa to 1000 kPa.
27. 27. The method of claim 26, wherein the pressure is applied to the first expansive material by a weight of the electrochemical cell.
28. 28. The method of claim 26 or 27, wherein the thermal management assembly is within a housing of a battery module, and the pressure is applied by a global thermal expansion of the thermal management assembly constrained by the housing.
29. 1. A method of manufacturing a thermal management assembly, comprising: providing a first intumescent material between the first electrochemical cell and the first heat exchange member; providing a second intumescent material between a second electrochemical cell and a second heat exchange member, said first and second intumescent materials being as claimed in any one of claims 1 to 28.